Extracellular matrix remodeling and TGF-β1/Smad signaling in diabetic colon mucosa - D'arpino, María Cecilia (2017)
Diabetes is associated with metabolic and functional alterations in the gut. Using an experimental model of streptozotocin (STZ)-induced diabetes in rodents, we analyzed the extracellular matrix (ECM) and TGF-β/Smad signaling in the colon mucosa. Male rats were divided into normal control, diabetic and insulin treated diabetic groups during 4 and 9 weeks. Sirius red staining showed marked increase in the extracellular matrix deposition in diabetic mucosa. High levels of fibrillar collagen (I and III) and fibronectin mRNAs were also detected with an imbalance between MMPs/TIMPs activities. Moreover, an increased mesenchymal cell proliferation together with an enhanced expression of myofibroblasts markers vimentin and α-SMA were observed. TGF-β/Smad signaling-related genes were determined using RT-PCR, Western blotting, and immunohistochemistry. Diabetic rats showed a significant up-regulation of TGF-β1, TGF-β receptors and the effectors p-Smad2/3 in the mucosa compared with control rats. Insulin treatment attenuated the stimulating effect of diabetes on colon ECM deposition and TGF-β/Smad signaling. In conclusion, the overall results showed a deregulation of the TGFβ1 pathway associated with the appearance of myofibroblasts and the accumulation of ECM in the mucosa of diabetic colon. These data provide the first in vivo evidence that TGF-β1/Smad is a key component of intestinal tissue remodeling in diabetes.